Effect of Ascophyllum nodosum, Sideritis scardica and Fucus vesiculosus Extracts on Germination, Initial Growth and Antioxidant Potential of Red Russian Kale Microgreens - Barbara Drygaś; Ewa Szpunar-Krok; Joanna Kreczko; Tomasz Piechowiak; Czesław Puchalski; Marta Jańczak-Pieniążek (Agriculture)
Natural plant- and algae-based extracts used in crop cultivation offer numerous advantages, including the potential to positively affect plant growth, exhibit hormonal activity, increase stress resistance, improve crop quality as environmentally benign alternatives to synthetic agrochemicals and help combat oxidative stress. The presented experiments aimed to compare the effectiveness of extracts from brown algae such as Ascophyllum nodosum and Fucus vesiculosus, as well as the plant Sideritis scardica, on the germination and initial growth of red kale (Brassica napus var. Pabularia) microgreens. Microgreens treated with aqueous extracts of A. nodosum, F. vesiculosus, as well as the control group, had the highest growth, whereas the lowest growth was observed in plants treated with water–ethanol extracts at the highest tested concentration (10%). The 10% water–ethanol extracts of brown algae reduced plant biomass, while aqueous extracts increased it. Applying water extracts of algae at concentrations (10, 1, 0.1%), as well as the water extract of S. scardica (10, 1%), led to an increase in the total phenolic content in the tested experimental groups. A significant influence on increasing total flavonoid content was noted for water extracts of F. vesiculosus at concentrations ranging from 0.1% to 10%. An opposite effect was observed for the water–ethanol extracts, where the lowest TFC was found in plants grown on mats soaked with 0.1% F. vesiculosus and 1% A. nodosum. All water–ethanol extracts tended to reduce the antioxidant activity of the tested red kale microgreens. In microgreens treated with water extracts of F. vesiculosus at concentrations of 1% and 10%, an increase in antioxidant activity was observed. Examining the impact of plant and algae extracts on kale germination and growth may provide valuable information on ways to improve the quality and health-promoting properties of kale microgreens.